Use of convex glass to improve driving safety in Sukahurip Village - Muhammad Aqmal Nurilshif Karim; Bravian Ariq Akbarulah; Katiah Katiah (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2024)
Driving safety is a severe challenge experienced by Sukahurip Village. In 2021, 306 accidents were recorded, especially on roads with sharp bends. The Sukahurip Village 2023 UPI KKN Student Team took the initiative through this service program to install convex mirrors on roads with sharp bends. The installation of this convex mirror as a 2023 UPI KKN student service program in Sukhurip Village is an effort to reduce the number of accidents and improve driving safety in Sukahurip Village. Another objective is to evaluate the impact of convex mirrors on improving traffic safety in rural areas. This service method is carried out through a direct approach in the area where the service is carried out by installing convex mirrors with a focus on broadening the driver's view and increasing awareness of road conditions. The results show a reduction in traffic accidents in the area because the convex mirror increases the viewing angle for the driver and allows a quicker response to road situations. This can certainly be a solution and a significant contribution for village communities to reduce the risk of accidents. The mirror installation involved collaboration between UPI 2023 KKN students and Sukahurip Village residents, providing concrete benefits for road safety in the village. It is hoped that one of the programs in this service activity can become the basis for similar programs regarding the importance of simple innovations such as convex mirrors in driving safety in rural areas.   Abstrak Keselamatan berkendara merupakan tantangan yang cukup serius dialami oleh Desa Sukahurip. Tercatat 306 kasus pada tahun 2021 kecelakaan terjadi, terutama di jalan dengan tikungan tajam. Tim Mahasiswa KKN UPI 2023 Desa Sukahurip berinisiatif melalui program pengabdian ini memasang cermin cembung di jalan dengan tikungan tajam. Pemasangan cermin cembung ini sebagai program pengabdian mahasiswa KKN UPI 2023 di Desa Sukhurip menjadi salah satu upaya untuk mengurangi angka kecelakaan yang terjadi serta meningkatkan keselamatan berkendara di Desa Sukahurip. Tujuan lainnya yaitu untuk mengevaluasi dampak penerapan cermin cembung terhadap peningkatan keselamatan lalu lintas di wilayah pedesaan. Metode pengabdian ini dilakukan melalui pendekatan secara langsung di daerah pelaksanaan pengabdian dengan memasang cermin cembung dengan fokus pada perluasan pandangan pengemudi dan peningkatan kesadaran terhadap kondisi jalan. Hasil menunjukkan pengurangan kecelakaan lalu lintas di daerah tersebut karena dengan cermin cembung meningkatkan sudut pandang bagi pengemudi dan memungkinkan respons yang lebih cepat terhadap situasi jalan. Hal ini tentunya bisa menjadi solusi dan kontribusi besar bagi masyarakat desa untuk mengurangi risiko terjadinya kecelakaan. Pemasangan cermin melibatkan kolaborasi antara mahasiswa KKN UPI 2023 dan warga Desa Sukahurip, memberikan manfaat konkret bagi keselamatan jalan di Desa tersebut. Diharapkan salah satu program pada kegiatan pengabdian ini dapat menjadi dasar bagi program lain yang sejenis mengenai pentingnya inovasi sederhana seperti cermin cembung dalam konteks keselamatan berkendara di daerah pedesaan. Kata Kunci: Cermin cembung; jalan dengan tikungan tajam; keselamatan berkendara